Reinterpreting published tDCS results in terms of a cranial and cervical nerve co-stimulation mechanism - Majdi, Alireza; Asamoah, Boateng; Mc Laughlin, Myles (Frontiers in Human Neuroscience, 2023)
Transcranial direct current stimulation (tDCS) is a non-invasive neuromodulation method that has been used to alter cognition in hundreds of experiments. During tDCS, a low-amplitude current is delivered via scalp electrodes to create a weak electric field in the brain. The weak electric field causes membrane polarization in cortical neurons directly under the scalp electrodes. It is generally assumed that this mechanism causes the observed effects of tDCS on cognition. However, it was recently shown that some tDCS effects are not caused by the electric field in the brain but rather via co-stimulation of cranial and cervical nerves in the scalp that also have neuromodulatory effects that can influence cognition. This peripheral nerve co-stimulation mechanism is not controlled for in tDCS experiments that use the standard sham condition. In light of this new evidence, results from previous tDCS experiments could be reinterpreted in terms of a peripheral nerve co-stimulation mechanism. Here, we selected 6 publications that reported tDCS effects on cognition and attributed the effects to the electric field in the brain directly under the electrode. We then posed the question: given the known neuromodulatory effects of cranial and cervical nerve stimulation, could the reported results also be understood in terms of tDCS peripheral nerve co-stimulation? We present our re-interpretation of these results as a way to stimulate debate within the neuromodulation field and as a food-for-thought for researchers designing new tDCS experiments.